2014
DOI: 10.1111/wrr.12151
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of advanced wound dressings for patients with chronic venous leg ulcers: A systematic review

Abstract: The purpose of this study was to systematically review the literature on the benefits and harms of advanced wound dressings on wound healing, mortality, quality of life, pain, condition of the wound bed, and adverse events for patients with chronic venous leg ulcers as compared with treatment with compression alone. We searched for primary studies in the databases of MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, and the Cumulative Index to Nursing and Allied Health Literature(®) from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 47 publications
(166 reference statements)
0
15
0
Order By: Relevance
“…Indeed, there is increased evidence that microbial biofilms are responsible for the chronic state of venous leg ulcers, diabetic foot ulcers, and pressure ulcers [35]. A number of wound dressings are available nowadays for local wound treatment most of which are based on silver [36,37]. To eradicate the biofilm, drug-releasing dressings should provide a long-term sustained release of drug.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is increased evidence that microbial biofilms are responsible for the chronic state of venous leg ulcers, diabetic foot ulcers, and pressure ulcers [35]. A number of wound dressings are available nowadays for local wound treatment most of which are based on silver [36,37]. To eradicate the biofilm, drug-releasing dressings should provide a long-term sustained release of drug.…”
Section: Introductionmentioning
confidence: 99%
“…What is clearly evident and highlighted in this article is that there is presently a lack of good scientific evidence regarding the efficacy of antimicrobial hydrogels on biofilms and healing rates. This area was reviewed recently by Valle and colleagues 49 who concluded that they did not identify any studies that assessed wound healing rates in a meaningful manner. Not only for hydrogels but for composite dressings, specialty absorptive dressings, contact layer dressings impregnated gauzes, or dressings with debriding agents.…”
Section: Discussionmentioning
confidence: 99%
“…Value begins with evidence-based medicine, and wound care is plagued by the paucity of well-designed, comparative clinical trials in welldefined patient cohorts. Despite a few prominent exceptions, most of the products for skin wounds lack adequate data on clinical outcomes, 105 which may be partly due to their approval along the device 510K regulatory pathway that does not require randomized controlled trials comparing them with standard of care, as well as the historical ability of products to achieve market access without such data. Moreover, even randomized studies in wound healing tend to be relatively small and lack an attempt at blinding, such as raters who are unaware of group assignment.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%